Synergy bags award, UMP clocks RM85k in book sales - UMP, PNC (Penerbit UMP, 2010)
The "Synergy" team from Universiti Malaysia Pahang's (UMP) Department of Research & Innovation (P&l) bagged the Promising Innovation Award at the 6"' Creative & Innovative Convention 2009/2010 with its proposed solution to "Managing & Marketing University's Academic Publications".